Edukasi Pencegahan Kekurangan Energi Kronik (KEK) Pada Ibu Hamil di Puskesmas Simpur Kota Bandar Lampung - Riska Wandini; Muhammad Rafli; Ilham Agung Sakti; Putri Yolanda Utama; Ni Luh Sumo; Novindri Ryalita; Mahda Rizka Faer Rifa’ie; Sumarni Sumarni; Yanti Fitria (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Pregnant women need nutrition to stay healthy. This is done by increasing and varying the food consumed, but do not increase the portion size and also limit the diet because it can harm the fetus in the womb. Chronic Energy Deficiency is a condition where a pregnant woman experiences a lack of food for a long period of time (chronic or chronic), giving rise to health problems such as being unable to meet the increased nutritional needs during pregnancy. Pregnant women who suffer from CED have a higher risk of giving birth with lower birth weight (LBW) than pregnant women without CED. The aim of this activity is to increase respondents' knowledge regarding how to prevent and treat CED. Socialization methods in the form of lectures and questions and answers are used in this activity using leaflets as media. Activity Results: Respondents were very enthusiastic about the material presented and there were several respondents who asked questions. The conclusion of this educational activity was successfully carried out to increase knowledge and awareness of pregnant women about the importance of preventing and treating Chronic Energy Deficiency Disorders (CED).